Integral part problems derived from a solution of an in mum problem - Pasteczka, Paweł; Száz, Árpád (Teaching Mathematics and Computer Science, 2018)
In this paper, we solve the following two integral part problems: Find all r ϵ R satisfying r^2 = [r]*([r]+1), resp. r^2≤[r]*([r]+1). These problems have been mainly motivated by a solution of an infimum problem of Z. Boros and Á. Száz.